Eutrophication reduced the release of dissolved organic carbon from tropical seagrass roots through exudation and decomposition. (July 2022) - Jiang, Zhijian; Li, Linglan; Fang, Yang; Lin, jizhen; Liu, Songlin; Wu, Yunchao; Huang, Xiaoping
Abstract: Seagrass bed ecosystem is one of the most effective carbon capture and storage systems on earth. Seagrass roots are the key link of carbon flow between leaf-root-sediment, and the release of dissolved organic carbon (DOC) from seagrass roots through exudation and decomposition are vital sources to the sediment organic carbon (SOC) in the seagrass beds. Unfortunately, human-induced eutrophication may change the release process of DOC from seagrass roots, thereby affecting the sediment carbon storage capacity. However, little is known about the effect of nutrient enrichment on the release of DOC from seagrass roots, hindering the development of seagrass underground ecology. Therefore, we selected Thalassia hemprichii, the tropical dominant seagrass species, as the research object, and made a comparison of the release of DOC from roots through exudation and decomposition under different nitrate treatments. We found that under control, 10 μmol L −1, 20 μmol L −1 and 40 μmol L −1 nitrate treatments, soluble sugar of T . hemprichii roots were 71.37 ± 3.43 mg g −1, 67.03 ± 5.33 mg g −1, 49.14 ± 3.48 mg g −1, and 18.51 ± 2.09 mg g −1, respectively, while the corresponding root DOC exudation rates were 7.00 ± 0.97 mg g DW root −1 h −1, 5.11 ± 0.42 mg g DW root −1 h −1, 4.08 ± 0.23 mg g DW root −1 h −1, and 3.78 ± 0.74 mg g DW root −1 h −1, respectively. There was a significant positive correlation between root soluble sugar and DOC exudation rate. DOC concentration of sediment porewater and SOC content also decreased under nitrate enrichment (though not significantly), which were both significantly positively correlated with the rate of root exuded DOC. Meanwhile, nitrate enrichment also reduced the release rate of DOC from seagrass roots during initial decomposition, and the release flux of DOC from decomposition. Therefore, nutrient enrichment could decrease nonstructural carbohydrates of seagrass roots, reducing the rate of root exuded DOC, thereby lowered SOC, as well as the DOC release from seagrass root decomposition. In order to increase the release of DOC from seagrass roots and improve the carbon sequestration capacity of seagrass beds, effective measures should be taken to control the coastal nutrients input into seagrass beds. Graphical abstract: Schematic diagram of the effects of nutrient enrichment on the release of dissolved organic carbon from seagrass roots. Image 1 Highlights: Effect of nitrate enrichment on the release of DOC from tropical seagrass roots. Nitrate enrichment reduced the rate of seagrass root exuded DOC. SOC was significantly positively correlated with the rate of root exuded DOC. Nitrate enrichment reduced the release of DOC from seagrass root decomposition. Nutrient inputs should be reduced to enhance seagrass carbon sequestration.